Toward a solar civilisation - "Aivanhov, Omraam Mikhael" (New Delhi, 2009)
Although we may know about heliocentricity from the point of view of astronomy, we are still far from having exhausted all its possibilities in the biological, psychological, cultural and spiritual spheres. The sun exists within each one of us and, if allowed to, can manifest its presence by awakening our consciousness to a global view of human problems
Keywords: Psychology